ANALISIS FREE CASH FLOW DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN PUBLIK DI INDONESIA - Susilawati, R. Anastasia Endang (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2010)
The main objective of this research is to examine behavior public company in Indonesia to manage of free cash flows and the role namagerial ownership on corporate debt policy. The using dependent variable on this research is debt, so independent variables are free cash flows and managerial ownership. The sample used was the public companies listed in the Jakarta Stock Exchange (JSX). There were 59 companies which have and during the period from 2005-2009. Data collected by purposive sampling. The result examination is that public company in Indonesia have low investment opportunity set (IOS) when free cash flow high attending by using debt for cost operation company. This result robust because evidence with chow test the result that significant difference regression stability between free cash flow to corporate debt policy have low and high investment opportunity set. Although, when dividend based big company have low investment opportunity and small company have low investment opportunity, both have the same effect between free cash flow on corporate debt policy. The result chow test suggest examination there are not statistically significant difference. Managerial ownership association negative with debt policy, this result evidence that agency cost of debt can be reduce by managerial ownership